Fish consumption in mid-childhood and its relationship to neuropsychological outcomes measured in 7–9 year old children using a NUTRIMENTHE neuropsychological battery. Issue 6 (December 2016) - ,; ,; Goyens, Philippe; Carlier, Clotilde; Hoyos, Joana; Poncelet, Pascale; Dain, Elena; Martin, Françoise; Xhonneux, Annick; Langhendries, Jean-Paul; Van Hees, Jean-Noel; Rousseaux, Deborah; et al.
Summary: Background: Long-chain polyunsaturated fatty acids (LCPUFA), particularly n-3 LCPUFA, play a central role in neuronal growth and the development of the human brain. Fish is the main dietary source of n-3 LCPUFA. To assess the relation between fish consumption, estimated dietary n-3 LCPUFA intake and cognition and behaviour in childhood in a multi-centre European sample. Methods: Children from 2 European studies, CHOP and NUHEAL, were assessed at 8 and 7.5 years of age, respectively. Different outcomes of neuropsychological development (assessed with the standardized NUTRIMENTHE Neuropsychological Battery (NNB) consisting of 15 subtests) were related with outcomes from a food-frequency questionnaire (FFQ) focussing on the consumption of fish. Results: A total of 584 children completed the FFQ and the neuropsychological tests. We found no associations with calculated DHA or EPA intakes for any of the neuropsychological domains. Children who consumed 2 fish meals per week including one of fatty fish, showed no substantive differences in the cognitive domains from the children who did not. However negative associations with fatty fish consumption were found for social problems (p = 0.019), attention problems (p = 0.012), rule-breaking problems (p = 0.019) and aggressive behaviour problems (p = 0.032). No association was observed with internalizing problems. Higher levels of externalizing problems (p = 0.018) and total problems (p = 0.018) were associated with eating less fatty fish. Conclusions: Children who consumed 2 fish meals per week including one of fatty fish were less likely to show emotional and behavioural problems than those who did not.